A Longitudinal Study of Symptoms of Oropharyngeal Dysphagia in an Elderly Community-Dwelling Population - Nimmons, Danielle; Michou, Emilia; Jones, Maureen; Pendleton, Neil; Horan, Michael; Hamdy, Shaheen (Dysphagia, 2016)
Dysphagia has been estimated to affect around 8–16 % of healthy elderly individuals living in the community. The present study investigated the stability of perceived dysphagia symptoms over a 3-year period and whether such symptoms predicted death outcomes. A population of 800 and 550 elderly community-dwelling individuals were sent the Sydney Swallow Questionnaire (SSQ) in 2009 and 2012, respectively, where an arbitrary score of 180 or more was chosen to indicate symptomatic dysphagia. The telephone interview cognitive screen measured cognitive performance and the Geriatric Depression Scale measured depression. Regression models were used to investigate associations with dysphagia symptom scores, cognition, depression, age, gender and a history of stroke; a paired t test was used to examine if individual mean scores had changed. A total of 528 participants were included in the analysis. In 2009, dysphagia was associated with age ( P = 0.028, OR 1.07, CI 1.01, 1.13) and stroke ( P = 0.046, OR 2.04, CI 1.01, 4.11) but these associations were no longer present in 2012. Those who had symptomatic dysphagia in 2009 ( n = 75) showed a shift towards improvement in swallowing ( P < 0.001, mean = −174.4, CI −243.6, −105.3), and for those who died from pneumonia, there was no association between the SSQ derived swallowing score and death ( P = 0.509, OR 0.10, CI −0.41, −0.20). We conclude that swallowing symptoms are a temporally dynamic process, which increases our knowledge on swallowing in the elderly.